A case report of clinical implications of a delayed antiretroviral therapy switch in a patient with multiple treatment interruptions. (December 2022) - Kakubu, Mireille A Mpalang; Frans, Kandali; Gibutai, Nelson; Katoto, Patrick DMC
The Namibia national antiretroviral therapy guidelines recommend that patients living with HIV who interrupt antiretrovirals and in the process disengage from care be restarted on their usual antiretroviral therapy regimen upon return. We introduce a 39-year-old male patient on first-line antiretroviral therapy, namely, tenofovir disoproxil fumarate, lamivudine and efavirenz, from 2015 to 2019 (4 years), who returned to care after the fourth episode of interrupting his treatment, though his adherence to antiretroviral therapy was deemed poor. Thus, he presented with severe immunosuppression and an AIDS-defining condition. Hence, he was switched to second-line antiretroviral therapy, treated with fluconazole for oesophageal candidiasis and reinitiated on cotrimoxazole prophylaxis. The client is currently clinically stable with a suppressed viral load. Medical and drug history taking with an emphasis on the previous history of treatment failure in patients returning to care are paramount in guiding the choice of future prescriptions of antiretrovirals. The multiple antiretroviral therapy interruptions from the patient and the delay in decision-making on the side of the clinician to switch treatments contributed to the emergence of an AIDS-defining condition.